Metabolomics-based analysis of dynamic metabolic trajectories and regulatory networks in two-stage fermentation of kiwifruit wine - Wangsheng Sun; Pengfei Bi; Wanju Yan; Rou Cai; Zhendong Zhang; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Jing Guo (Food Microbiology, 2027)

Oxalate-assisted formation mechanism of lignocellulose-based two-dimensional porous carbon and its application in zinc-ion hybrid capacitors - Xiaotong Ma; Xiaohao Liu; Lijie Sun; Rui Diao; Dongxu Yan; Zhenting Zha; Liangyuan Jia; Fenglei Qi; Zhitao Zhang; Yingcui Fang; Peiyong Ma (Bioresource Technology, 2026)

Concept design, simulation and image reconstruction of gamma-ray emission computed tomography (GECT) for non-destructive inspection of nuclear fuel assemblies - Zhanfei Liu; Jingru Chen; Mingfei Yan; Xubin Zhang; Lucheng Yang; Wenxuan Zhang; Rui Jia; Huasi Hu (Annals of Nuclear Energy, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Balancing fermentation control and aroma complexity in semi-spontaneous kiwifruit fermentation through Saccharomyces cerevisiae inoculum level - Wanju Yan; Yuanjing Li; Zitong Zhang; Rou Cai; Sinuo Feng; Jia Han; Wangsheng Sun; Rui Cai; Zhouli Wang; Jing Guo (Food Research International, 2026)

Effect of double-cropping pattern on biological yield and quality of silage corn across different cropping systems in the Hebei region - Liang Song; Min Jia; Quanguo Zhang; Jianghao Wang; Liwei Wang; Rui Guo; Yuanyuan Yan; Jianfeng Wei; Xinghua Li; Wei Song (Next Research, 2026)

Description of two novel Marinobacter species isolated from saline-alkali soil: Marinobacter alkalisoli sp. nov. and Marinobacter shunpengi sp. nov - Jing-Yan Zhao; Lian Xu; Rui-Qi Sun; Mei-Qian Song; Jia-Hui Zeng; Hua-Mei Wei; Ji-Quan Sun (Systematic and Applied Microbiology, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Dietary ellagic acid improves glucose and lipid homeostasis with concurrent gut microbiota and serum metabolome remodeling in db/db mice - Rui-Bo Jia; Weipei Li; Pengru Yan; Chunxia Zhou; Zirui Huang; Mouming Zhao (Food Bioscience, 2026)

Subchronic PM2.5 exposure exacerbates chronic stress-induced depression-like pathology in mice - Haoyu Lu; Xiaohui Zhao; Ran Ning; JunKoo Yi; Zhongmei He; Yan Zhao; Jianan Geng; Jia Zhou; Weijia Chen; Rui Du (Environmental Research, 2026)

Corrigendum to “In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota” [Carbohydrate Polymers 339 (2024) 122255] - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Effect of first-stage anode axial position on discharge characteristics of a double-stage anode layer thruster - Rui Ding; Sheng Wen; Zhihao Liu; Jia Liu; Guanrong Hang; Yan Zhang; Ximing Zhu; Yongjie Ding (Advances in Space Research, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Rhizosphere microbiome and soil health effects on ginseng growth performance and ginsenoside accumulation - Jing Fang; Rui Liu; Kemeng Zhang; Yingmei Sun; Yan Xue; Changbao Chen; Tao Zhang; Qinghe Zhang; Jia Chen (Plant and Soil, 2026)

Fe-N-C-supported LaFeO3 heterojunction electrodes for efficient copper and fluoride removal in symmetric capacitive deionization - Shaojian Xie; Yujia Wang; Rui Zhang; Lei Huang; Jia Yan; Zhenxin Chen; Hongguo Zhang; Meng Li; Hongbo Zeng (Water Research, 2026)

Carbonate-retaining multilayer Co(OH)2@FeOOH electrodes enable superior stability in seawater oxygen evolution: Sustaining 5000 h at 1 A cm−2 - Yingxia Wei; Zhangwei Li; Farhat Nosheen; Xueyan Wu; Rui Xue; Xingyun Li; Yan Lv; Jixi Guo; Dianzeng Jia (Chemical Engineering Journal, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Corrigendum to “Flow backward alleviated the river algal blooms” [Volume 245, 15 October 2023, 120593] - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Editor's note “Phosphorus – the main limiting factor in riverine ecosystems in China” [Sci. Total Environ. 870 (2023) 161613] - Yan Chen; Jie Chen; Rui Xia; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

RNF125 promotes CD8 T cell-mediated anticancer immunity and suppresses the malignant phenotype of cervical cancer - Di Yang; Jia Liu; Yan Gao; Xin Guan; Rui Tong (Molecular and Cellular Biochemistry, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Construction and textural modification of soft surimi gel from spanish mackerel (Scomberomorus niphonius) by polysaccharides - Yin-Yin Lv; Xian-Hao Zhang; Jia-Ni Zhou; Ying-Rui Wang; Zhu-Jun Zhang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2026)

Contamination risk assessment of shallow groundwater in Xi'an City's plain area based on groundwater vulnerability, pollution loading, and groundwater function value - Yan Liu; Jialu Pang; Weiwei Hu; Zhifeng Jia; Jia Chen; Hao Liu; Rui Lei (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

The effect of minimum temperatures on changes in river dissolved oxygen is more pronounced in the climate transition zone - Qin Zhang; Rui Xia; Kai Zhang; Haiming Li; Yan Chen; Ruining Jia; Jinghui Dou; Lina Li; Chao Yan; Xiang Li (Journal of Environmental Management, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

MXene triggers room-temperature 4D printing of advanced ionic hydrogels for sensitive electronic skin - Qinglong He; Chendong Zhao; Yuanjie Jiang; Jimei Liu; Xinyu Liu; Rui Jia; Cheng Yang; Mengzhou Liao; Yan Zhao; Desheng Kong; Valeria Nicolosi; Caofeng Pan; et al. (Chemical Engineering Journal, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Formation mechanism analysis of karst collapses in Geleshan Town-Zhongliang Town, Chongqing, China - Yuanbin Wu; Rui Cao; Jia Wang; Yan Meng; Renchao Yin; Zhikui Liu (Carbonates and Evaporites, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Fossil involucres and a nutlet of Ostrya (Betulaceae) from the upper Eocene of Shaanxi and their biogeographic implications - Jiao Huang; Hui Jia; Rui-Feng Yan; Xiang-Ning Meng; Zhuo-Chen Han; Tian-Qi Dong; Jian Pan; Cheng Quan (Palaeoworld, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Research on calibration transfer methods in coal quality spectral analysis across instruments and coal types - Jiaxuan Li; Jiaxin Yin; Rui Gao; Yan Zhang; Lei Zhang; Lei Dong; Weiguang Ma; Wangbao Yin; Suotang Jia (Analytica Chimica Acta, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Construction of multiscale high entropy oxide nanofibers and their room temperature gas-sensitive properties: a synergistic DFT theoretical and experimental study - Rui Yang; Xinmei Li; Zhiqi Yan; Liming Jia (Chemical Engineering Journal, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

Tailoring porous carbon from optimized coal blends for high-performance supercapacitor electrodes - Yanli Zhu; Tao Wang; Yan Ma; Rui Sheng; Pengxu Ren; Jia Guo; Dianzeng Jia; Dongling Wu (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Low-damage performance of rocking column bases with Belleville Springs for enhanced seismic resilience - Jiang-Yue Xie; Zhenduo Yan; Junrong Liu; Rui Zhang; Ping Xiang; Xianzhong Zhao; Gregory A. MacRae; G. Charles Clifton; Rajesh P. Dhakal; Shahab Ramhormozian; Geoffrey Rodgers; Pierre Quenneville; et al. (Engineering Structures, 2025)

Lightweight, compressible and superhydrophobic coal-based nanofibrous/graphene oxide composite aerogel towards efficient oil and organic solvents adsorption - Yanchun Pei; Xueyan Wu; Zhichao Ren; Yan Lv; Rui Xue; Xin Luo; Jixi Guo; Dianzeng Jia (Desalination, 2025)

Portable intelligent digital microfluidic system for rapid antibiotic susceptibility testing - Caiwei Li; Yibo Qi; Stephanie Andaluz; Nan Shi; Yan Lu; Pui-in Mak; Rui P. Martins; Yanwei Jia (Chemical Engineering Journal, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Revealing the key role of interfacial oxygen activation over CoMn2O4@MnO2 in the catalytic oxidation of acetone - Cangpeng Shan; Yan Zhang; Ning Hou; Qinwei Jia; Xinyu Hou; Yunchong Wang; Rui Han; Caixia Liu; Weichao Wang; Qingling Liu (Journal of Hazardous Materials, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Prediction of sandstone porosity in coal seam roof based on variable mode decomposition and random forest method - Ya-ping Huang; Xue-mei Qi; Yan Cheng; Ling-ling Zhou; Jia-hao Yan; Fan-rui Huang (Applied Geophysics, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Effects of microplastics on soil physicochemical properties and vertical migration and transformation of chromium - Jia-li Li; Na-ying Li; Jia Ni; Rui-lin Wan; Jin-yan Yang (Journal of Environmental Chemical Engineering, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Portulaca oleracea L. polysaccharide ameliorates ulcerative colitis by regulating the immune system and gut microbiota - Yang Yang; Xiechen Zhou; Guiyan Jia; Hui Zhao; Yan Li; Junyang Cao; Zijian Guan; Rui Zhao (Food Bioscience, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

The potential regulatory role of the non-coding RNAs in regulating the exogenous estrogen-induced feminization in Takifugu rubripes gonad - Xufang Shen; Hongwei Yan; Mingtao Hu; Huiting Zhou; Jia Wang; Rui Gao; Qi Liu; Xiuli Wang; Ying Liu (Aquatic Toxicology, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Long-term global water pollution stress from crops production considering different driving forces - Chi Ma; Zhongwen Yang; Wenchao Sun; Rui Xia; Ruining Jia; Lu Wang; Yan Chen (Sustainable Production and Consumption, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

3D-interconnected N-doped porous carbon with hierarchical pore structure as a high-efficiency catalyst for H2S oxidation at room temperature - Yan Huang; Qiang Zuo; Rui Wang; Ruifang Zhang; Yike Zhang; Jia Song; Jingzhen Wang; Boqiang Gao; Shuanglong Ma (Journal of Cleaner Production, 2024)

Hierarchical conducting networks constructed as resistive strain sensors for personal healthcare monitoring and robotic arm control - Huijuan Lin; Jia Wang; Wei Cao; Huinan Wang; Kun Rui; Yan Yan; Jixin Zhu (Chemical Engineering Journal, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Cytotoxicity sesquiterpenoids from the leaves of Datura stramonium L. - Juan Pan; Yan Liu; Ao-Fei Wang; Jia-Tong Wu; Rui Yang; Wei Guan; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Somatic Embryogenesis in Taxodium Hybrid ‘zhongshanshan’, an Opportunity to Propagate an Ecologically Friendly Species - Tingting Chen; Xiaoyu Jia; Rui Zhang; Yan Lu; Chaoguang Yu; Yunlong Yin; Jianfeng Hua; David Creech (Journal of Plant Growth Regulation, 2024)

Mechanisms of the novel pesticide sodium dodecyl benzene sulfonate in the mitigation of protozoan ciliated pathogens during microalgal cultivation - Gaojingwen Sun; Ruiqi Jia; Yan Zhang; Zhaoji Zhang; Yunlong Wang; Rui Ma; Yaxin Wang; Zhiyang Jiang; Mingjian Liu; Yong Jiang (Marine Pollution Bulletin, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Predictions of seismic response for sheet-pile wall in liquefiable deposit within LEAP 2022 using the CycLiq constitutive model - Bin Hu-Yan; Rui Wang; Jia-ke Yu; Jian-Min Zhang (Soil Dynamics and Earthquake Engineering, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

Telluribacter roseus sp. nov., Isolated from the Kumtag Desert Soil - Chu-Ying Feng; Jia-Rui Han; Chun-Yan Lu; Li Gu; Shuai Li; Wen-Hui Lian; Lei Dong; Wen-Jun Li (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Flow backward alleviated the river algal blooms - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2023)

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Non-steady state fluctuations in water levels exacerbate long-term and seasonal degradation of water quality in river-connected lakes - Yingze Yin; Rui Xia; Yan Chen; Ruining Jia; Nixi Zhong; Chao Yan; Qiang Hu; Xiang Li; Hui Zhang (Water Research, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Tax scheme for agricultural technology innovation incentive - Zi-rui Chen; Jia-yi Guo; Pu-yan Nie (Paddy and Water Environment, 2023)

Experimental study on low-damage performance of Sliding Hinge Joint - Junrong Liu; Rui Zhang; Zhenduo Yan; Jiang-Yue Xie; Kim Eng Chouery; Liang-Jiu Jia; Ping Xiang; Xianzhong Zhao; Shahab Ramhormozian; Rajesh P. Dhakal; G. Charles Clifton; Gregory A. MacRae (Soil Dynamics and Earthquake Engineering, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Heterogeneity of molecular-level and photochemical of dissolved organic matter derived from decomposing submerged macrophyte and algae - Jia He; Lixin Jiao; Guoqiang Zhi; Xue Wu; Yan Yang; Shuai Ding; Jinlong Zheng; Zhi Shao; Rui Xia (Journal of Environmental Management, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Morphological brain alterations in dialysis- and non-dialysis-dependent patients with chronic kidney disease - Huan Yu; Chaoyang Zhang; Yan Cai; Ning Wu; Xiuqin Jia; Jiaojiao Wu; Feng Shi; Rui Hua; Qi Yang (Metabolic Brain Disease, 2023)

An improved light use efficiency model by considering canopy nitrogen concentrations and multiple environmental factors - Helin Zhang; Jia Bai; Rui Sun; Yan Wang; Zhiqiang Xiao; Bowen Song (Agricultural and Forest Meteorology, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Kidney Mesenchymal stem cells alleviate cisplatin-induced kidney injury and apoptosis in rats - Rui-ning Liang; De-qi Yan; Xing-ping Zhang; Xu Chen; Wen-hui Zhang; Hong-lin Jia (Tissue and Cell, 2023)

Sodium hydrosulfide alleviates aluminum toxicity in Brassica napus through maintaining H2S, ROS homeostasis and enhancing aluminum exclusion - Yan Yu; Jia Dong; Rui Li; Xue Zhao; Zonghe Zhu; Fugui Zhang; Kejin Zhou; Xianyong Lin (Science of The Total Environment, 2023)

Estimating the magnitude of early Permian relative sea-level changes in southern North China - Rui Ma; Jianghai Yang; Yuan Wang; Jiaxin Yan; Jia Liu (Global and Planetary Change, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Spatial distribution and quantitative source identification of nutrients and beneficial elements in the soil of a typical suburban area, Beijing - Qin-Rui Zhang; Sheng-Qiang Zhang; Yong Huang; Huan Li; Yan-Hui Jia; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Discussion of the Tax Scheme for Cleaner Water Use - Jia-yi Guo; Zi-rui Chen; Pu-yan Nie (Water Conservation Science and Engineering, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Compounding soils to improve cropland quality: A study based on field experiments and model simulations in the loess hilly-gully region, China - Yun-xin Huang; Zheng-jia Liu; Yan-sui Liu; Yu-rui Li; Xue-qi Liu (Journal of Mountain Science, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Gisenoside Rg1 attenuates cadmium-induced neurotoxicity in vitro and in vivo by attenuating oxidative stress and inflammation - Teng-Teng Ren; Jia-Ying Yang; Jun Wang; Sheng-Rui Fan; Rongfeng Lan; Xiao-Yan Qin (Inflammation Research, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

The regional difference in engineering-control and tillage factors of Chinese Soil Loss Equation - Rui-yin Chen; Dong-chun Yan; An-bang Wen; Zhong-lin Shi; Jia-cun Chen; Yuan Liu; Tai-li Chen (Journal of Mountain Science, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

The complete chloroplast genome of Saxifraga sinomontana (Saxifragaceae) and comparative analysis with other Saxifragaceae species - Yan Li; Liukun Jia; Zhihua Wang; Rui Xing; Xiaofeng Chi; Shilong Chen; Qingbo Gao (Brazilian Journal of Botany, 2019)
Saxifraga sinomontana J.-T. Pan & Gornall belongs to Saxifraga sect. Ciliatae subsect. Hirculoideae , a lineage containing ca. 110 species whose phylogenetic relationships are largely unresolved due to recent rapid radiations. Analyses of complete chloroplast genomes have the potential to significantly improve the resolution of phylogenetic relationships in this young plant lineage. The complete chloroplast genome of S. sinomontana was de novo sequenced, assembled and then compared with that of other six Saxifragaceae species. The S. sinomontana chloroplast genome is 147,240 bp in length with a typical quadripartite structure, including a large single-copy region of 79,310 bp and a small single-copy region of 16,874 bp separated by a pair of inverted repeats (IRs) of 25,528 bp each. The chloroplast genome contains 113 unique genes, including 79 protein-coding genes, four rRNAs and 30 tRNAs, with 18 duplicates in the IRs. The gene content and organization are similar to other Saxifragaceae chloroplast genomes. Sixty-one simple sequence repeats were identified in the S. sinomontana chloroplast genome, mostly represented by mononucleotide repeats of polyadenine or polythymine. Comparative analysis revealed 12 highly divergent regions in the intergenic spacers, as well as coding genes of matK , ndhK , accD , cemA , rpoA , rps19 , ndhF , ccsA , ndhD and ycf1 . Phylogenetic reconstruction of seven Saxifragaceae species based on 66 protein-coding genes received high bootstrap support values for nearly all identified nodes, suggesting a promising opportunity to resolve infrasectional relationships of the most species-rich section Ciliatae of Saxifraga .

Synthesis and antitumor evaluation of novel fused heterocyclic 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazole derivatives - Xiao-Jia Liu; Hai-Ying Liu; Hai-Xin Wang; Yan-Ping Shi; Rui Tang; Shuai Zhang; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

De Novo Assembled Transcriptome Analysis and Identification of Genic SSR Markers in Red-Flowered Strawberry - Yan Ding; Li Xue; Rui-xue Guo; Gang-jun Luo; Yu-tong Song; Jia-jun Lei (Biochemical Genetics, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Least squares reverse-time migration in the pseudodepth domain and reservoir exploration - Xiao-Dong Sun; Yan-Rui Jia; Min Zhang; Qing-Yang Li; Zhen-Chun Li (Applied Geophysics, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Variable-grid reverse-time migration of different seismic survey data - Xiao-Dong Sun; Zhen-Chun Li; Yan-Rui Jia (Applied Geophysics, 2017)

Automatic event detection in low SNR microseismic signals based on multi-scale permutation entropy and a support vector machine - Rui-Sheng Jia; Hong-Mei Sun; Yan-Jun Peng; Yong-Quan Liang; Xin-Ming Lu (Journal of Seismology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Degradation of recalcitrant aliphatic and aromatic hydrocarbons by a dioxin-degrader Rhodococcus sp. strain p52 - Hai-Yan Yang; Rui-Bao Jia; Bin Chen; Li Li (Environmental Science and Pollution Research, 2014)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Field response of aboveground non-target arthropod community to transgenic Bt-Cry1Ab rice plant residues in postharvest seasons - Yao-Yu Bai; Rui-Hong Yan; Gong-Yin Ye; Fangneng Huang; David S. Wangila; Jin-Jun Wang; Jia-An Cheng (Transgenic Research, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Complete genomic sequence analyses of Turnip mosaic virus basal-BR isolates from China - Hong-Yan Wang; Jin-Liang Liu; Rui Gao; Jia Chen; Yun-Hua Shao; Xiang-Dong Li (Virus Genes, 2009)

A new dolabellane diterpenoid from the Hainan soft coral Spongodes sp. - Xiao-Hong Yan; Rui Jia; Xu Shen; Yue-Wei Guo (Natural Product Research, 2007)

An experimental study of the mechanisms of freeze/thaw and wind erosion of ancient adobe buildings in northwest China - Jian-Jun Qu; Guo-Dong Cheng; Ke-Cun Zhang; Jia-Cheng Wang; Rui-Ping Zu; Hai-Yan Fang (Bulletin of Engineering Geology and the Environment, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Production and analysis of transgenic wheat (Triticum aestivum L.) with improved insect resistance by the introduction of cowpea trypsin inhibitor gene - Rui-Ming Bi; Hai-Yan Jia; De-Shun Feng; Hong-Gang Wang (Euphytica, 2006)